Developing the capacity of school management to build understanding of vision and mission - dwi sukaningtyas; Djam’an Satori; Udin Syaefudin Sa’ud (Journal of Education and Learning (EduLearn), 2019)
In many schools, the vision mission just "exist" and not become a guideline especially implementation of learning. The school just execute school routine without knowing the meaning of implementation. This is unfortunate, because the vision and mission is a unique destination that covers the activity and can be utilized as the power of quality of the service organization. How is the capacity of school management in developing the vision and mission? The goal of the research is to describe and analyze the capacity of school management in developing the vision and mission. This study used a qualitative approach with case studies. Data collection methods used are interviews, observation, and study of the document/artifact. The validity of the data is done with credibility, transferability, dependability, and confirmability. The results shows that schools which establish vision and mission based on noble values of the founders have a strong base for the development.